2018
DOI: 10.1016/j.jamda.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Can Sepsis Be Detected in the Nursing Home Prior to the Need for Hospital Transfer?

Abstract: NHs need better systems to monitor NH residents whose status is changing, and to present that information to medical providers in real time, either through rapid medical response programs or telemetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 34 publications
0
27
1
Order By: Relevance
“… 6 , 42 In particular, one-quarter of patients who died with sepsis initially presented from long-term care facilities and it is unknown to what degree earlier recognition and care could have mitigated poor outcomes. 43 This is an important topic for future research.…”
Section: Discussionmentioning
confidence: 97%
“… 6 , 42 In particular, one-quarter of patients who died with sepsis initially presented from long-term care facilities and it is unknown to what degree earlier recognition and care could have mitigated poor outcomes. 43 This is an important topic for future research.…”
Section: Discussionmentioning
confidence: 97%
“…Our results showed that the daily risk of readmission was relatively stable across 30 days, highlighting the need for close monitoring and follow-up throughout the early post-discharge period. However, one study suggested that nursing homes need better systems to monitor residents with fluctuating clinical status, since over 25% of residents transferred to a hospital did not have vital signs documented and over 80% were not seen by a medical provider (physician, nurse practitioner, or physician assistant) in the 72 hours before hospital transfer [ 40 ]. Implementing processes to detect changes in clinical status may be particularly important for SNF residents following a hospitalization for pneumonia or sepsis, since septicemia was the most common cause of hospital readmission in our study population, and sepsis and septic shock are medical emergencies that require rapid diagnosis and immediate intervention [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Providers are rarely on site; so, a substantial proportion of treatment decisions are made without a physician, nurse practitioner, or physician assistant examining the patient. 29,30 Adding to the challenge of obtaining an adequate assessment is the fact that the majority of NH residents have cognitive impairment 31 and that on-site laboratory testing is rarely available. 32 In such decision-making situations, medical providers tend to overvalue antibiotics and underestimate their adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…They house complex, frail residents, in whom infections can evolve rapidly and present atypically . Providers are rarely on site; so, a substantial proportion of treatment decisions are made without a physician, nurse practitioner, or physician assistant examining the patient . Adding to the challenge of obtaining an adequate assessment is the fact that the majority of NH residents have cognitive impairment and that on‐site laboratory testing is rarely available .…”
Section: Discussionmentioning
confidence: 99%